Pengaruh Penerapan Sistem Informasi Akuntansi Dan Integritas Terhadap Kinerja Karyawan - Aghlul Jannatun; Endang Masitoh W; Rosa Nikmatul Fajri (Universitas Batanghari Jambi, 2021)
This study attempts to examine and analyse the effects application of Accounting information system (AIS) and integrity to employee performance . The population of the research is all employees of Amil Zakat Institution Yatim Mandiri in 2020. The testing of hypotheses in this research using multiple linear regression analysis with t test, F test and the coefficient of determination (Adjusted R2). The sample collection method in this study is purposive sampling. Based on the research , it is know application of Accounting information system (AIS) influences in employee performance. The better application of Accounting information system (AIS) will be also improve employee performance. The integrity influences in employee performance, with the integrity owned by employees to improve employee performance in finishing work responsibilities.